Transmembrane and Ubiquitin-Like Domain-Containing 1 Promotes Glioma Growth and Indicates Unfavorable Prognosis - Yinggang Liu; Changcheng Cai; Ke Wu; Libo Hu (International Journal of Genomics)
Background. Ubiquitin-related proteins have garnered increasing attention for their roles in tumorigenesis. Transmembrane and ubiquitin-like domain-containing 1 (TMUB1) is a recently discovered protein in the ubiquitin-like domain family, yet its involvement in glioma remains poorly understood. This study is aimed at investigating the functional significance and clinical relevance of TMUB1 in glioma. Methods. We conducted a comprehensive analysis using two cohorts: a retrospective glioma cohort from our hospital and The Cancer Genome Atlas (TCGA) cohort. The mRNA levels of TMUB1 were assessed through reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Clinical associations of TMUB1 in these cohorts were evaluated using correlation tests, chi-square tests, and survival analyses. Additionally, we performed TMUB1 knockdown in U87 and LN-229 human glioma cell lines, and cellular growth was assessed through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Results. Our results revealed that TMUB1 expression was elevated in glioma tissues compared to normal brain tissues. Notably, lower TMUB1 expression correlated with favorable characteristics such as lower World Health Organization (WHO) grade and 1p/19q codeletion. Moreover, patients with higher TMUB1 levels in glioma tissues exhibited worse prognosis in both TCGA cohort and our retrospective cohort, underscoring its prognostic significance in gliomas. Cellular experiments demonstrated that TMUB1 silencing suppressed the growth of glioma cells. Conclusions. TMUB1 emerges as a novel and clinically relevant prognostic biomarker for gliomas. Targeting TMUB1 holds promise as a potential strategy for glioma treatment. This study contributes valuable insights into the multifaceted role of TMUB1 in glioma pathogenesis and its potential as a diagnostic and therapeutic target.